Analysis of learning components in implementation of educational process in schools - Azka Widhiasti; Anggie Putri; Muhammad Adnan Fanani; Najwa Salim; Yandhy Rizky Kurnia (Curricula: Journal of Curriculum Development, 2022)
Indonesian education has undergone many changes in line with the changes in the applied curriculum. This affects educators in carrying out teaching and learning activities so that they must quickly adapt to implementing the new curriculum, provide understanding to students, and guide them to adapt to the system. When the curriculum changes, the essential things in learning also change according to the change in curriculum, namely the learning components. Learning in its process has elements that are related and influence each other. The learning component includes objectives, materials, media, strategies, and evaluation. As time goes by and changes in technology, aspects of learning components change into a form of adjustment. Elements of the learning component turned into a state of adjustment. This study aims to look back at the learning components when the new curriculum is implemented in schools. The research method uses qualitative methods with library research. The result of this study is that the learning components when the new curriculum is implemented have some differences in the application of aspects of the learning components.